Key Factors of Efficient Operator Activities (Belügyi Szemle, 2024)
Aim: The study aims to explore the role and significance of human factors and cognitive processes in the operator activities of surveillance systems.Methodology: The authors discuss important human factors related to effective video surveillance and the environmental conditions necessary for efficient work, drawing observations from various research studies and standards.Findings: The sensory, perceptual, and attentional abilities of the operator have a significant impact on the quality of their activities. The efficient operation of surveillance systems largely depends on the operators’ intuition, expertise, and the appropriate work environment.Value: The study contributes to a better understanding of the role of human factors in video surveillance systems and allows us to formulate guidelines and recommendations that can improve the efficiency of operator activities.